Hypothermia as a treatment option for hypoxic-ischemic encephalopathy in newborns – A literature review - Urbaś, Weronika; Artykiewicz, Klaudia; Czarkowski, Marcin; Gorczyca, Kamila; Grodkiewicz, Maria; Kozieł, Paweł; Krzysiek, Urszula; Podgórska, Klaudia; Puła, Aleksandra; Słupczyńska, Aleksandra (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Neonatal asphyxia is a medical condition in which the neonate is not able to maintain sufficient respiratory function. The hypoxia may be caused by either an impaired respiratory activity of the neonate or an interruption of blood flow to the placenta in the period immediately before or during delivery, which resulted in inadequate oxygen perfusion to vital organs. Description of the state of knowledge: Hypoxic-ischaemic encephalopathy (HIE) is a form of perinatal hypoxia, occurring in newborns after the 35th week of gestation and presenting along with neurological disorders. In fact, it is a major cause of death and infant disability. The incidence of HIE is approximately 2-5 per 1000 live births. The standard recommended treatment for perinatal hypoxic-ischaemic encephalopathy is therapeutic hypothermia. There are two methods used: selective head cooling with moderate whole-body hypothermia (SHC) and whole-body hypothermia (WBC). In both cases, metabolism and neural tissue destruction are slowed down. Conclusions: Therapeutic hypothermia is a promising treatment option for neonatal encephalopathy. Thus, it decreases the risk of death and neurological deficits in the form of cerebral palsy, epilepsy and psychomotor retardation. Whole-body hypothermia appears to be a more successful method than selective head cooling, however more research is still needed.